Analisis Empiris Kemungkinan Penghindaran Pajak di Perguruan Tinggi - Alfani, Feralda Septya; Rahman, Afrizal; Attsani, Adi Purnomo; Najmudin, Nandang (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
Taxes are a source of state income which is used to finance government spending and national development, so taxes have an important role in the development of the Indonesian economy. But taxpayers always want to pay as little tax as possible, whereas for the government taxes are the main source of national income, so Tax Avoidance occurs. This research aims to examine the influence of Love of Money, Religiosity and Gender on Tax Avoidance. In addition, this study examines the legal loopholes that some universities might potentially exploit for tax avoidance. The method in this research uses a literature review, namely research that finds theories and analyzes them. This research found that: 1) Love of Money influences Tax Avoidance; 2) Religiosity influences Tax Avoidance and; 3) Gender influences Tax Avoidance; 4) Legal loopholes that universities might exploit for tax avoidance. Keywords: Love of Money; Religiosity; and Tax Avoidance.